Photodegradation of congo red in aqueous solution by using advanced oxidation process (aops) technique / Ninna Sakina Azman - Azman, Ninna Sakina (Faculty of Applied Sciences, 2017)
Congo Red (CR) is one of the complicated azo dyes which consist of three N=N double bonds. Significantly, to degrade the dyes contained in the waste water, it is necessary to choose the best method. The method that had been used in this project is advanced oxidation process or best known as AOPs method. The AOPs method used was divided into two which are Fenton process and Heterogeneous photocatalytic reaction. The Heterogeneous photocatalytic reaction which participate the present of TiO2/UV shows a great degradation rate compared to the Fenton process with the present of Mn2+/H2O2/UV. This is because, only small volume of TiO2 needed to degrade the CR compared to the Mn2+/H2O2. This is prove with 0.00133 mol of both TiO2 catalyst and Fenton reagent, the present of TiO2 catalyst already provide the 98.32% compared to Fenton reagent which only 87.58% of percentage degradation. The highest dye removal efficiency in both AOPs method were obtained in the acidic medium, pH 3 with time taken 90 minutes and with the highest concentration of Mn2+ and mass of TiO2 which are 0.05 M, 99.92% and 0.339 g, 98.82% respectively. FTIR on the elimination of the N=N double bonds in chemical structure of CR also had been studied. Furthermore, factors that affect the photocatalytic degradation also been studied which were concentration of CR, concentration of H2O2, concentration of Mn2+, mass of TiO2 and lastly the effect of pH.